A comprehensive review of known and emerging viruses infecting rose species - Paslay, Caleb; Ali, Akhtar (Frontiers in Virology, 2025)
Roses have been cultivated by humans for centuries. They play an essential role in the horticulture industry by contributing economically, enhancing landscape aesthetics, supporting pollinators and other wildlife. However, roses are susceptible to viral diseases. More than thirty known and emerging plant viruses have been directly identified in rose plants worldwide. Emerging viruses pose a potential threat to the cultivation of roses. These viruses are taxonomically diverse, primarily belonging to the Bromoviridae, Betaflexiviridae, Secoviridae and Tospoviridae families, with the Ilarvirus, Nepovirus, and Orthotospovirus genera being most common. Most of these viruses are positive-sense single-stranded (+ssRNA) or negative-sense single-stranded (-ssRNA) and have segmented genomes, while only two DNA viruses have been reported in roses. Transmission of these viruses occurs via arthropod vectors (n=16), as well as through vegetative propagation, grafting, and nematodes. Current virus management strategies focus on early detection and removal of infected plants to prevent virus spread. This review provides a comprehensive overview of the geographical distribution, transmission mechanisms of viruses infecting roses, and molecular properties of virus genomes offering valuable insights for growers and researchers. This review may help in developing targeted strategies for virus management and emphasizes the importance of continued collaboration to improve viral disease management in roses.